Quantum Otto engine driven by quantum fields - Gallock-Yoshimura, Kensuke; Thakur, Vaishant; Mann, Robert B. (Frontiers in Physics, 2023)
We consider a quantum Otto engine using an Unruh-DeWitt particle detector model which interacts with a quantum scalar field in curved spacetime. We express a generic condition for extracting positive work in terms of the effective temperature of the detector. This condition reduces to the well-known positive work condition in the literature under the circumstances where the detector reaches thermal equilibrium with the field. We then evaluate the amount of work extracted by the detector in two scenarios: an inertial detector in a thermal bath and a circulating detector in the Minkowski vacuum, which is inspired by the Unruh quantum Otto engine.